First report of pre-Hispanic Fasciola hepatica from South America revealed by ancient DNA - Beltrame, Maria Ornela (2019)
It is generally assumed that the digenean human liver fluke, Fasciola hepatica, gained entry to South America during the 15th century upon arrival of Europeans and their livestock. Nonetheless in Patagonia, Argentina, digenean eggs similar to F. hepatica have been observed in deer coprolites dating back to 2300 years B.P. The main objective of our present study was to identify and characterize these eggs using an ancient DNA (aDNA) study. Eggs were isolated and used for aDNA extraction, amplification and sequencing of partial regions from the cytochrome c oxidase subunit 1 and the nicotinamide adenine dinucleotide dehydrogenase subunit 1 mitochondrial genes. Also, phylogenetic trees were constructed using Bayesian and maximum likelihood. Our results confirm the presence of F. hepatica in South America from at least 2300 years B.P. This is the first report and the first aDNA study of this trematode in South America prior to the arrival of the European cattle in the 15th century. The present work contributes to the study of phylogenetic and palaeobiogeographical aspects of F. hepatica and its settlement across America.